A Population-Based Model to Consider the Effect of Seasonal Variation on Serum 25(OH)D and Vitamin D Status. (1st September 2015) - Vuistiner, Philippe; Rousson, Valentin; Henry, Hugues; Lescuyer, Pierre; Boulat, Olivier; Gaspoz, Jean-Michel; Mooser, Vincent; Vollenweider, Peter; Waeber, Gerard; Cornuz, Jacques; Paccaud, Fred; Bochud, Murielle; et al.
Abstract : Background . We elaborated a model that predicts the centiles of the 25(OH)D distribution taking into account seasonal variation. Methods . Data from two Swiss population-based studies were used to generate (CoLaus) and validate (Bus Santé) the model. Serum 25(OH)D was measured by ultra high pressure LC-MS/MS and immunoassay. Linear regression models on square-root transformed 25(OH)D values were used to predict centiles of the 25(OH)D distribution. Distribution functions of the observations from the replication set predicted with the model were inspected to assess replication. Results . Overall, 4, 912 and 2, 537 Caucasians were included in original and replication sets, respectively. Mean (SD) 25(OH)D, age, BMI, and % of men were 47.5 (22.1) nmol/L, 49.8 (8.5) years, 25.6 (4.1) kg/m 2, and 49.3% in the original study. The best model included gender, BMI, and sin-cos functions of measurement day. Sex- and BMI-specific 25(OH)D centile curves as a function of measurement date were generated. The model estimates any centile of the 25(OH)D distribution for given values of sex, BMI, and date and the quantile corresponding to a 25(OH)D measurement. Conclusions . We generated and validated centile curves of 25(OH)D in the general adult Caucasian population. These curves can help rank vitamin D centile independently of when 25(OH)D is measured.